An Expedient Synthesis of Carbazoles through Potassium tert‐Butoxide‐Promoted Intramolecular Direct C–H Bond Arylation. Issue 3 (21st December 2016) - Lin, Songbo; He, Xingrui; Meng, Jinpeng; Gu, Haining; Zhang, Peizhi; Wu, Jun
Abstract : Transition‐metal‐free access to carbazoles was achieved through base‐mediated intramolecular C–C bond formation. Reactions of N ‐substituted o ‐halodiarylamines with potassium tert ‐butoxide in the presence of ethylene glycol or 1, 10‐phenanthroline provided carbazoles in moderate to excellent yields. This transformation may proceed through a radical pathway according to a control experiment with a radical scavenger. Abstract : Facile access to carbazoles through intramolecular C–H arylation from readily accessible N ‐substituted o ‐halodiarylamines under transition‐metal‐free conditions is reported. The intramolecular direct C–C cross‐coupling of N ‐substituted o ‐iododiarylamines proceeds under mild conditions (30 °C) by using ethylene glycol as a cheap and nontoxic additive.